Atlas of clinical ophthalmology - Basak, Samar K. (Jaypee Brothers Medical Publishers, 2013)
With the current rapid development of ophthalmic sciences, it is difficult for ophthalmologists to remain fully up to date with all areas of clinical specialty. The second edition of this atlas describes the latest advances in clinical ophthalmology. Each chapter deals with a separate part of the eye, discussing different diseases and disorders that may be encountered by ophthalmologists. Each condition is accompanied by concise descriptions of major and minor signs, as well as detailed photographs illustrating the disease. This comprehensive new edition features 3750 full colour images and illustrations, including more than 600 additional photographs. Images from the first edition have been replaced with better quality photographs taken with the Haag-Streit BX-900 Photo-Slit Lamp and the Zeiss FF 450 Plus Fundus camera.